The basic helix-loop-helix transcription factor SHARP1 is an oncogenic driver in MLL-AF6 acute myelogenous leukemia - Akihiko Numata (Nature Portfolio, 2018)
Gene fusions involving MLL and different partner genes define unique subgroups of acute myelogenous leukemia, but the mechanisms underlying specific subgroups are not fully clear. Here the authors elucidate the mechanisms of MLL-AF6 induced transformation, providing a distinct pathway that involves SHARP1 as a critical target.